2009
DOI: 10.1038/sj.bjc.6605149
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cohort study on sun habits and endometrial cancer

Abstract: BACKGROUND: No large cohort study has examined the risk of endometrial cancer in relation to sun exposure. METHODS: A population-based cohort study of 29 508 women who answered a questionnaire in 1990 -92, of whom 24 098 responded to a follow-up enquiry in 2000 -02. They were followed for an average of 15.5 years. RESULTS: Among the 17 822 postmenopausal women included, 166 cases of endometrial cancer were diagnosed. We used a multivariate Cox regression analysis adjusting for age and other selected demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…However, according to recent cohort and case-control studies circulating 25(OH)D levels may play an important role in the development of pancreatic, lung, endometrial, ovarian, and other cancers [8,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 98%
“…However, according to recent cohort and case-control studies circulating 25(OH)D levels may play an important role in the development of pancreatic, lung, endometrial, ovarian, and other cancers [8,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 98%
“…77 A study in Boston found higher bone mass density among sunbed users. 74 Two recent studies from Sweden found reduced risk of disease associated with use of sunbeds more than three times a year for endometrial cancer 78 and thrombotic events. study only claims association, not causality, and the criteria for causality do not appear to be satisfied.…”
mentioning
confidence: 99%
“…Fish contain omega-3 fatty acids and vitamin D (30). Several previous studies showed that vitamin D reduced the risk of endometrial cancer (31,32). It has been reported that vitamin D inhibits endometrial cancer cell growth by upregulating semaphorin 3B and 3F, as well as prevents obesity-induced endometrial cancer (33,34).…”
Section: Discussionmentioning
confidence: 97%